2016
DOI: 10.1094/cchem-04-16-0108-fi
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular and Micronutrient Profiles of Sprouted Chickpeas to Be Used for Integrating Cereal‐Based Food

Abstract: Cereal Chem. 94(1):82-88Pulse flour may be used to improve nutritional traits of gluten and glutenfree formulations in traditional food such as bread or pasta. However, owing to some intrinsic nutritional, textural, and sensory properties, the use of pulses as ingredients for production of enriched food remains limited. In this study, we investigated the modification in macromolecules and micronutrients in industrial-scale flour from partially sprouted chickpeas to define its possible use as an ingredient in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Germination results in the reduction of antinutrients, increases micronutrient bioavailability, and improves the sensory properties of pulses (Marengo et al., ). Commercial systems that combine partial germination with a drying process permit germinated grains to be milled into various types of flours (Bellaio, Kappeler, Rosenfeld, & Jacobs, ).…”
Section: Grain Legumes Entering the Millmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination results in the reduction of antinutrients, increases micronutrient bioavailability, and improves the sensory properties of pulses (Marengo et al., ). Commercial systems that combine partial germination with a drying process permit germinated grains to be milled into various types of flours (Bellaio, Kappeler, Rosenfeld, & Jacobs, ).…”
Section: Grain Legumes Entering the Millmentioning
confidence: 99%
“…In one such study, Marengo et al. () observed that germination of chickpea (3 days at 18 to 24 °C followed by drying at 50 °C for 10 hr) resulted in reorganization of storage proteins (increased concentrations of solubilized proteins and accessible thiols); the modified proteins produced better dough mixing properties for the sprouted chickpea flour. Furthermore, the starch and ash contents decreased in the sprouted chickpea flour (yield of 90% compared to unsprouted chickpea).…”
Section: Grain Legumes Entering the Millmentioning
confidence: 99%
“…Consequently, the resulting bread will be characterized by low volume and sticky and gummy crumb . Controlled sprouting might thus be a useful process to achieve the perfect balance between nutritional advantages and technological performance . In this context, Grassi et al .…”
Section: Introductionmentioning
confidence: 99%
“…3 Controlled sprouting might thus be a useful process to achieve the perfect balance between nutritional advantages and technological performance. 4 In this context, Grassi et al proposed the use of a portable Micro Near Infrared (NIR) device to monitor the sprouting process. 5 Although the study was carried out at lab scale (1 kg of kernels), the analysis of the spectra suggested that the greatest changes in both starch (1480-1526 nm) and protein (1500-1530 nm) fractions occurred in the first 48 h, whereas longer germination time generated no further relevant changes.…”
Section: Introductionmentioning
confidence: 99%
“…starch digestibility) (Erba et al, 2018). In addition, flour from germinated chickpeas improved nutritional and rheological characteristics in enriched cereal-based foods (Marengo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%